A new zeolitic lithium aluminum imidazolate framework - Jiang, Guangshen; Bon, Volodymyr; Xu, Fei; Garai, Bikash; Zhang, En; Senkovska, Irena; Poetke, Stephanie; Hippauf, Felix; Hausdorf, Steffen; Paasch, Silvia; Brunner, Eike; Wang, Hongqiang; et al. (Dalton Transactions, 2021)
An aliovalent mixed-metal framework DUT-174 [LiAl(2-methylimidazolate)4]n, isostructural to ZIF-8, was synthesized from lithium aluminum hydride (LiAlH4) and 2-methylimidazole (2-mImH) through dehydrogenation. Lithium and aluminum cations acting as alternating framework nodes are coordinated tetrahedrally by (2-mIm)-. DUT-174 has a high specific surface area of 1149 m2g−1and CO2uptake of 11.57 mmol g−1at 195 K.
CRIS-Team Scopus Importer:2022-04-14